Analisis Dampak Inflasi Kelompok Volatile Food terhadap Konsumsi Rumah Tangga di Provinsi Jambi Periode 2020-2024 - Nadia Atika Sari; Nurisnaini Ashuratirana; Rahmad Mardianto; Miftahul Jannah; Miranda Herdia Nova; Ahmad Setiawan Nuraya (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study aims to analyze the impact of volatile food inflation on household consumption in Jambi Province during 2020–2024. The research employed a descriptive qualitative method using secondary data obtained from Statistics Indonesia (BPS), Bank Indonesia, and related literature. The results show that volatile food inflation fluctuated significantly, with the highest inflation recorded in 2021 at 18.12% and deflation occurring in 2023 at -8.71%. Although household consumption continued to increase, rising food prices affected consumption patterns and reduced people’s purchasing power, especially among low-income households. Therefore, food price stability is essential to maintain household consumption and public welfare.